Domain homologues of dopamine beta-hydroxylase and ferric reductase: roles for iron metabolism in neurodegenerative disorders? - Ponting, C (2001)
One of the defining characteristics of neurodegenerative diseases, including Parkinson's, Alzheimer's and Huntington's diseases, is abnormal accumulations of iron, specifically in affected areas. Following injection of iron in rat brains, a relatively selective lesion of dopamine neurons, similar to parkinsonism, occurs. These observations indicate that Fe(II)-mediated generation of free radical species, by the Fenton reaction, might contribute to the pathoetiology of these diseases. Iron is known to possess multiple roles in the biosynthesis of catecholamines in dopaminergic neurons. These include, as Fe(II), facilitating the production of dopamine from phenylalanine by tyrosine hydroxylase, and as heme, assisting the recycling of ascorbate by cytochrome b-561 required for the generation of norepinephrine from dopamine by dopamine beta-hydroxylase. In this study, it is demonstrated that a human and mouse gene product, stromal cell-derived receptor 2, is a homologue of cytochrome b-561 and duodenal cytochrome b, and is thus predicted to be active as a ferric reductase. Moreover, this protein also contains a domain homologous to the N-terminal regulatory region of dopamine beta-hydroxylase. These findings from sequence analysis lead to a prediction that stromal cell-derived receptor 2 is a catecholamine-regulated ferric reductase active in the brain. Dysfunction of cytochrome b-561 or stromal cell-derived receptor 2, therefore, might predispose individuals to abnormal accumulation of Fe(III) and/or generation of cytotoxic free radicals as a consequence of a rapid cycling between Fe(III) and Fe(II). The hypothesis that aberrant ferric reductase activities are involved in the progression of neurodegenerative diseases should open up new avenues of research, and possibly therapy, for these devastating diseases.